Dietary exposure and biomarkers of arsenic in consumers of fish and shellfish from France - Sirot, V.; Guérin, T.; Volatier, J.-L.; Leblanc, J.-C. (The Science of the total environment, 2009)
Seafood, especially fish, is considered as a major dietary source of arsenic (As). Seafood consumption is recommended for nutritional properties but contaminant exposure should be considered. The objectives were to assess As intake of frequent French seafood consumers and exposure via biomarkers. Consumptions of 996 high consumers (18 and over) of 4 coastal areas were assessed using a validated food frequency questionnaire. Seafood samples were collected according to a total diet study (TDS) sampling method and analyzed for total As, arsenite (AsIII), arsenate (AsV), arsenobetaïne (AsB), monomethylarsonic acid (MMA) and dimethylarsinic acid (DMA). The average As dietary exposure is 94.7 ± 67.5 μg/kg bw/week in females and 77.3 ± 54.6 μg/kg bw/week in males ( p < 0.001) and the inorganic As dietary exposure is respectively 3.34 ± 2.06 μg/kg bw/week and 3.04 ± 1.86 μg/kg bw/week ( p < 0.05). Urine samples were collected from 382 of the subjects. The average urinary As concentration is 94.8 ± 250 μg/g creatinine for females and 59.7 ± 81.8 μg/g for males ( p < 0.001). Samples having an As concentration above 75 μg/g creatinine ( n = 101) were analyzed for inorganic As (As(III), As(V), MMA(V) and DMA(V)) which was 24.6 ± 27.9 μg/g creatinine for males and 27.1 ±20.6 μg/g for females. Analyses do not show any correlation between dietary exposure and urinary As. These results show that biological results should be interpreted cautiously. Diet recording seems to be the best way to assess dietary As exposure. Seafood is a high source of As exposure but even among high consumers it is not the main source of toxic As. From a public health point of view these results should be interpreted carefully in the absence of international consensus on the health-based guidance value.